Batik Science Demonstration Program (PODESABA) for the Enlightened Generation at the Sanggar Muhammadiyah in Kampung Baru, Kuala Lumpur, Malaysia - Anugrah Ricky Wijaya; Aman Santoso; Eli Hendrik Sanjaya; Dima Vici Nadia Ariefianti; Intan Ainul Malik; Dewinta Yuka Siwi; Fatmah Khairani; Novida Pratiwi; Ratna Yunita Setiyani Subardjo; Ahmad Sururi (Department of Chemistry, Universitas Negeri Malang, 2025)
The Batik Science Demonstration Program (PODESABA) for the Enlightened Generation was conducted by the Department of Chemistry's community service team at Sanggar Muhammadiyah, Kampung Baru, Kuala Lumpur, Malaysia, in 2025. This international community service initiative aimed to introduce fundamental chemistry concepts through culturally contextualised learning, enhancing students' scientific literacy and creativity. The program comprised four main sessions: (1) a redox reaction demonstration using Betadine solution and citrus juice to visualize vitamin C presence, (2) a simple paper chromatography experiment to illustrate separation techniques, (3) an ecoprint batik workshop utilizing plant-based dyes and alum solution as a natural mordant, and (4) a jumput (tie-dye) batik activity using natural dyes. Each activity was designed to be interactive and culturally relevant, enabling participants to connect scientific principles with traditional batik-making practices. The program yielded positive outcomes, including heightened enthusiasm and active participation among children, improved comprehension of redox and separation concepts, and the creation of innovative batik products. This initiative successfully integrated science and art, embodying the spirit of The Enlightened Generation through cross-cultural collaboration and exchange.